Increased uncoupling protein-2 and -3 mRNA expression during fasting in obese and lean humans. - Millet, L; Vidal, H; Andreelli, F; Larrouy, D; Riou, J P; Ricquier, D; Laville, M; Langin, D (The Journal of Clinical Investigation, 1997)
Uncoupling protein-2 and -3 (UCP2 and UCP3) are mitochondrial proteins that show high sequence homology with the brown adipocyte-specific UCP1. UCP1 induces heat production by uncoupling respiration from ATP synthesis. UCP2 is widely expressed in human tissues, whereas UCP3 expression seems restricted to skeletal muscle, an important site of thermogenesis in humans. We have investigated the regulation of UCP2 and UCP3 gene expression in skeletal muscle and adipose tissue from lean and obese humans. UCP2 and -3 mRNA levels were not correlated with body mass index (BMI) in skeletal muscle, but a positive correlation (r = 0.55, P < 0.01, n = 22) was found between UCP2 mRNA level in adipose tissue and BMI. The effect of fasting was investigated in eight lean and six obese subjects maintained on a hypocaloric diet (1,045 kJ/d) for 5 d. Calorie restriction induced a similar 2-2.5-fold increase in UCP2 and -3 mRNA levels in lean and obese subjects. To study the effect of insulin on UCP gene expression, six lean and five obese subjects underwent a 3-h euglycemic hyperinsulinemic clamp. Insulin infusion did not modify UCP2 and -3 mRNA levels. In conclusion, the similar induction of gene expression observed during fasting in lean and obese subjects shows that there is no major alteration of UCP2 and -3 gene regulation in adipose tissue and skeletal muscle of obese subjects. The increase in UCP2 and -3 mRNA levels suggests a role for these proteins in the metabolic adaptation to fasting.